BATAS WILAYAH DAN DINAMIKA PENJAGAAN BATAS LAUT DI INDONESIA DALAM DIMENSI SOSIOKULTURAL - Marsetio, Marsetio (Faculty of Humanities, Diponegoro University, 2013)
ABSTRACT This paper discusses about boundaries concept and the dynamics of sea boundaries in Indonesian. As an archipelagic state with a very potential resources, unfortunately Indonesia does not have an